A relational approach to understanding inhabitants' engagement with Photovoltaic (PV) technology in homes - Frances, Ziyad; Stevenson, Fionn (Architectural science review, 2020)
Photovoltaic (PV) systems have been promoted in the UK housing sector as a key strategy for meeting carbon reduction commitments by offsetting the use of the non-renewable grid energy with renewable energy. However, inhabitants are not changing their routine energy consumption practices to take advantage of off-grid day time solar energy and, in some cases, even shifting practices away from the initial intentions underlying the technology. This means that the necessary energy savings from new housing are not being achieved. In this paper, this is attributed to the variation in the provisioning of PV technology in new homes, as well as inhabitants' engagement with and know-how of PV technologies, subject to explicit rules and policies. The key contribution of this paper is to reveal how PV technologies and inhabitants interact within different socio-technological home contexts drawing on Practice theory and ethnographic methods applied to four housing developments in England.